1986
DOI: 10.1159/000215351
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Double-Blind Comparison between Fragmin and Conventional Low-Dose Heparin: Thromboprophylactic Effect and Bleeding Complications

Abstract: In a randomized, prospective, double-blind multicenter trial, the effect of low-dose conventional heparin (5,000 IU/12 h) was compared to a low molecular weight (LMW) heparin fragment (5,000 antifactor Xa U/24 h). 432 patients 40 years or older undergoing elective abdominal surgery were included, 382 correctly treated. 45% had malignant diseases. The groups did not differ in risk factors. Analysis was made both on the basis of intention to treat and correct prophylaxis. No difference in results between these 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 13 publications
0
11
0
3
Order By: Relevance
“…No appropriate experi mental human model seems to exist. Clinical experience indicates that bleeding is a major side effect, not only of the traditional unfrac tionated heparin, but also of the new, low molecular weight heparins [ 19]. Whether the antithrombotic/haemorrhagic effect ratio in man is improved by the low molecular weight heparins is so far not clearly estab lished.…”
Section: Discussionmentioning
confidence: 99%
“…No appropriate experi mental human model seems to exist. Clinical experience indicates that bleeding is a major side effect, not only of the traditional unfrac tionated heparin, but also of the new, low molecular weight heparins [ 19]. Whether the antithrombotic/haemorrhagic effect ratio in man is improved by the low molecular weight heparins is so far not clearly estab lished.…”
Section: Discussionmentioning
confidence: 99%
“…Kabi 2165 and other LM W heparins have been shown to be effective and safe prepara tions for the prophylaxis of DVT in several groups of immobilized patients when used in doses according to their individual anticoag ulant and bleeding properties [18][19][20][21][22][23]. In general surgical patients (less prone to de velop DVT compared to stroke patients) an effective and safe dose of Kabi 2165 seems to be 2,500 anti-Xa U s.c./24 h [24,25], Turpie et al [26] used LMW heparin ORG10172 in stroke patients to prevent DVT and concluded that treated patients developed less DVT and did not suffer from major bleeding accidents.…”
Section: Discussionmentioning
confidence: 99%
“…In ad dition, most of the reported bleeding studies were carried out in the intravenous acute studies. The LMW heparins are generally used in the subcutaneous prophylaxis of ve nous thrombosis over a period of 7-15 days [21,22], The bleeding models, therefore, must be consistent with this mode of therapy and the data must be carefully evaluated. Utilizing the rabbit ear bleeding index mod el, we studied the bleeding effects of various LMW heparins and calculated the bleeding index for each of the agents.…”
Section: Discussionmentioning
confidence: 99%